The Relationship of Antral Follicle Count (AFC) with Levels of Estradiol Serum and Mature Ovarian Follicles in Women Undergoing the IVF Program at the Graha Amerta Fertility Clinic of General Hospital of Dr. Soetomo in the Period 2018 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: In the last two decades, one of the critical factors of assisted reproductive technology (ART)has been identified as ovarian capacity. Consequently, ovarian capacity markers have evolved to be part ofdiagnostic testing conducted regularly before IVF. Several predictor factors, such as antral follicle count(AFC), is one of several factors to predict ovarian capacity. These diagnostic procedures and tests have thepurpose of identifying women at high-risk patient who respond poorly toward controlled ovarian stimulationthroughout the IVF cycle. The ovarian response toward ovulation stimulation within this research was assessedby peak estradiol (E2) serum levels and the total number of mature follicles. There is no clear relationshipbetween AFC and levels of estradiol serum and the number of mature ovarian follicles to identify womenwho respond poorly. Methods: This study is an analytical study with a cross-sectional design. Samples weretaken from secondary data of medical records using the total sampling method on women undergoing the IVFprogram at the Graha Amerta fertility clinic of General Hospital of Dr. Soetomo from January 1 to December31 2018 according to the inclusion and exclusion criteria. The AFC variables, estradiol serum levels, and thenumber of mature ovarian follicles in the study were analyzed using Spearman’s correlation. Conclusion:There is a significant relationship between antral follicle count (AFC) with the levels of estradiol serum andthe number of mature follicles in women undergoing the IVF program.
Keywords: Antral follicle count (AFC), estradiol (E2) serum levels, the number of mature ovarian follicles